1998
DOI: 10.1016/s0014-5793(98)00812-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of double‐stranded oligonucleotides containing reactive acylphosphate internucleotide groups

Abstract: DNA duplex and dumbbells containing chemically active acylphosphate internucleotide groups were synthesized. To obtain these compounds the chemical ligation method was used. The acylphosphate group was inserted into a DNA duplex and dumbbells as a result of template-directed condensation of 5P-phosphate and especially introduced 3P-carboxy groups of oligonucleotides. 1-Ethyl-3-(3P-dimethylaminopropyl)carbodiimide (EDC) was used as a condensing agent. Oligonucleotides containing a carboxy group were obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Methyl acetyl phosphate is known to inactivate several enzymes by acylation (22). The electrophilic properties of acyl phosphates have also been used in a number of applications such as cross-linking reagents for hemoglobins (23) and the affinity modification of DNA-recognizing proteins (24). Little research has been reported for acyl phosphates of di-and triphosphates.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl acetyl phosphate is known to inactivate several enzymes by acylation (22). The electrophilic properties of acyl phosphates have also been used in a number of applications such as cross-linking reagents for hemoglobins (23) and the affinity modification of DNA-recognizing proteins (24). Little research has been reported for acyl phosphates of di-and triphosphates.…”
Section: Resultsmentioning
confidence: 99%